Análise de falhas em pistão de motor à combustão quatro tempos turbo - Sato, Daniel Mitsumassa Rama (Universidade Federal de São Carlos, 2024)
With the automotive turbocharger market experiencing a significant increase due to lower CO2 emission limits and growing demand for high-performance vehicles, the market is predicted to grow from 32.28 billion dollars in 2022 to 64.69 billion of dollars by 2032. In this context, studies of failures in supercharged engines with turbochargers are of great value to ensure safety, efficiency, performance and compliance with regulations, thus contributing to the continuous improvement of the automotive industry. This work focuses on understanding the metallurgical aspects associated with piston failures in internal combustion engines, using as a case study a piston failure in a supercharged four-stroke alcohol engine, used in the Formula SAE student competition. The objective was to understand how some of the failures occur in supercharged internal combustion engines for further studies and developments in the automotive sector. Through metallography techniques, scanning electron microscopy, Vickers microhardness and thermodynamic simulations, it was possible to obtain information on how known faults develop in engines such as ring microwelding and piston melting from a metallurgical perspective and thus observe that, for a hypereutectic Al alloy -Si with an approximate content of 24% by mass of Si, critical failures such as microwelding of sealing rings and pulling out of materials in pistons, in certain cases, end up being a consequence of less severe failures such as melting of the piston head after a melting process dynamic and specific.
Failure analysis of a turbocharged 4-stroke combustion engine piston
Keywords: Análise de falha; Pistão; Ligas alumínio silício; Failure analysis; Piston; Al-Si alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA